A temperature characterization of (Si-FinFET) based on channel oxide thickness - Yousif Atalla; Yasir Hashim; Abdul Nasir Abd Ghafar; Waheb A. Jabbar (Universitas Ahmad Dahlan, 2019)
This paper presents the temperature-gate oxide thickness characteristics of a fin field-effect transistor (FinFET) and discusses the possibility of using such a transistor as a temperature nano-sensor. The investigation of channel oxide thickness–based temperature characteristics is useful to optimized electrical and temperature characteristics of FinFET. Current–voltage characteristics with different temperatures and gate oxide thickness values (Tox = 1, 2, 3, 4, and 5 nm) are initially simulated, and the diode mode connection is considered to measure FinFET’s temperature sensitivity. Finding the best temperature sensitivity of FinFET is based on the largest change in current (∆I) within a working voltage range of 0–5 V. According to the results, the temperature sensitivity of FinFET increases linearly with oxide thickness within the range of 1–5 nm, furthermore, the threshold voltage and drain-induced barrier lowering increase with increasing oxide thickness. Also, the subthreshold swing (SS) is close to the ideal value at the minimum oxide thickness (1 nm) then increases and diverges with increasing oxide thickness. So, the best oxide thickness (nearest SS value to the ideal one) of FinFET under the conditions described in this research is 1 nm.